Risk of HIV Acquisition Among Men Who Have Sex With Men Infected With Bacterial Sexually Transmitted Infections: A Systematic Review and Meta-Analysis. Issue 10 (October 2021) - Malekinejad, Mohsen; Barker, Erin K.; Merai, Rikita; Lyles, Cynthia M.; Bernstein, Kyle T.; Sipe, Theresa Ann; DeLuca, Julia B.; Ridpath, Alison D.; Gift, Thomas L.; Tailor, Amrita; Kahn, James G.
Abstract : Background: Men who have sex with men (MSM) who have bacterial sexually transmitted infections (STIs) are at increased risk for HIV infection. We enhanced and updated past summary risk estimates. Methods: We systematically reviewed (PROSPERO No. CRD42018084299) peer-reviewed studies assessing the risk of HIV infection among MSM attributable to Chlamydia trachomatis (CT), Mycoplasma genitalium (MG), Neisseria gonorrhoeae (NG), Treponema pallidum (TP), and/or Trichomonas vaginalis (TV). We searched 3 databases through December 2017. We excluded studies with self-reported data or simultaneous STI and HIV assessment. We conducted dual screening and data extraction, meta-analytically pooled risk ratios (RRs), and assessed potential risk of bias. Results: We included 26 studies yielding 39 RR ( k ) for HIV acquisition due to one of TP, NG, or CT. We did not identify eligible data for MG or TV, or for HIV transmission. HIV acquisition risk increased among MSM infected with TP ( k = 21; RR, 2.68, 95% confidence interval [CI], 2.00–3.58), NG ( k = 11; RR, 2.38; 95% CI, 1.56–3.61), and CT ( k = 7; RR, 1.99; 95% CI, 1.59–2.48). Subanalysis RRs for all 3 pathogens were ≥1.66 and remained statistically significant across geography and methodological characteristics. Pooled RR increased for data with the lowest risk of bias for NG ( k = 3; RR, 5.49; 95% CI, 1.11–27.05) and TP ( k = 4; RR, 4.32; 95% CI, 2.20–8.51). We observed mostly moderate to high heterogeneity and moderate to high risk of bias. Conclusions: Men who have sex with men infected with TP, NG, or CT have twice or greater risk of HIV acquisition, although uncertainties exist because of data heterogeneity and risk of bias. Abstract : This review highlights the temporal relationship between sexually transmitted infection and HIV for men who have sex with men. Results indicate that men who have sex with men infected with Treponema pallidum, Neisseria gonorrhoeae, or Chlamydia trachomatis have twice or greater risk of HIV acquisition.Supplemental digital content is available in the text.